Vlasov simulation of the emissive plasma sheath with energy-dependent secondary emission coefficient and improved modeling for dielectric charging effects - Sun, Guang-Yu; Zhang, Shu; Guo, Bao-Hong; Sun, An-Bang; Zhang, Guan-Jun (Frontiers in Physics, 2022)
A one-dimensional Vlasov-Poisson simulation code is employed to investigate the plasma sheath considering electron-induced secondary electron emission (SEE) and backscattering. The SEE coefficient is commonly treated as constant in a range of plasma simulations, here improved SEE model of a charged dielectric wall is constructed which includes the wall charging effect on SEE coefficient and the energy dependency of SEE coefficient. Pertinent algorithms to implement above SEE model in plasma simulation are studied in detail. It is found that the SEE coefficient increases with the amount of negative wall charges, which in turn reduces the emissive sheath potential. With energy-dependent SEE coefficient, the sheath potential is a nonlinear function of the plasma electron temperature, as opposed to the linear relation predicted by classic emissive sheath theory. Simulation combining both wall charging effect and SEE coefficient’ energy dependency suggests that the space-charged limited sheath is formed at high plasma electron temperature levels, where both sheath potential and surface charging saturate. Additionally, different algorithms to implement the backscattering in kinetic simulation are tested and compared. Converting backscattered electron to secondary electron via an effective SEE coefficient barely affects the sheath properties. The simulation results are shown to be commensurate with the upgraded sheath theory predictions.